Analisis Kemampuan Numerasi Siswa SMA dalam Memecahkan Masalah Ditinjau dari Motivasi Belajar pada Materi Matriks - Mia Wulansari; Dina Prasetyowati; Irene Andita Purnamasari (Journal on Education, 2024)
The aim of this research is to analyze the numeracy abilities of high school students in solving mathematics problems on matrix material in terms of learning motivation. The research method used is a mixed method carried out collaboratively. This research was conducted at SMA Negeri 9 Semarang with research subjects totaling 36 class XI-4 students. The data in this research was collected through the use of motivational questionnaires, interviews and observations. Data collection was analyzed quantitatively descriptively, with data analysis techniques divided into quantitative and qualitative analysis. The subjects in this research were two class XI-4 students, each of whom represented high and medium levels of learning motivation. Based on the results of this research, it was concluded that students with moderate levels of learning motivation can fulfill all indicators, namely being able to utilize various numbers and symbols related to basic mathematics, analyze the information presented, and interpret the results of the analysis to predict and make decisions. Meanwhile, students with moderate levels of learning motivation can only fulfill two indicators, namely they can only utilize various numbers and symbols related to basic mathematics, analyze the information presented.